Pengembangan Modul Ajar Berbasis Pembelajaran Berdiferensiasi Pada Materi â€œMenggunakan Dataâ€ - Titin Suryani; Syarifah Fadillah Al Hadad; Jamilah Jamilah (J-PiMat : Jurnal Pendidikan Matematika, 2023)
This research is by using research and development (RnD) method. The model used is the 3-D model approach or development, which stands for Define, Design, and Development. The purpose of this research is to develop teaching modules based on differentiated learning on material using data. The research subjects were 20 students of class VII SMP Assalam Pontianak Islamic Boarding School. Data analysis techniques used are interviews, indirect communication techniques, and measurement scatter hitam techniques. The instruments used in this study were test sheets for learning outcomes, validation sheets, and response questionnaires. Differentiation-based teaching modules have media and material validity levels of 90.26% and 83.58%, respectively, in the "very valid" category. From the questionnaire filled out by the teacher and students, the practicality value of the teacher and student response questionnaire was 100% and 90.5% respectively with the "very practical" category. The effectiveness of the module is seen from the results of student learning using the t test. It can be seen from the results of the t test which shows that tcount (2.2202649) > ttable (2.0930241) which means Ha is accepted where learning outcomes after being given learning with teaching modules based on learning differ beyond KKM score is 73..